Predicting Caries in Medical Settings: Risk Factors in Diverse Infant Groups - Fontana, M. (J Dent Res, 2018)
Expanded partnership with the medical community is a promising strategy for reducing disparities in dental caries among young children. However, no validated caries risk instrument exists for use in primary health care settings. To help resolve this gap, a 52-item caries risk questionnaire was developed and targeted to primary caregivers (PCGs) to test in a 3-y prospective study. To begin to understand the validity of the questionnaire items, the purpose of this study was to compare responses to the questionnaire based on key demographic characteristics known to be associated with disparities in caries experience (e.g., race/ethnicity and insurance status). A total of 1,323 one-year-old children were recruited primarily through 3 medical research networks. Baseline questionnaire responses were analyzed via logistic regression. The sample was 49% female. Its racial/ethnic makeup was as follows: 13% Hispanic, 37% White, 37% Black, and 13% other or multiracial. Sixty-one percent were enrolled in Medicaid, and 95% resided in urban communities. Mothers represented 94% of PCGs. There were significant differences (P < 0.05) in baseline responses based on Medicaid status and race/ethnicity. As compared with those not enrolled in Medicaid, children in the Medicaid group were significantly more likely (after adjusting for race/ethnicity) to 1) go to sleep while nursing or drinking something other than water, 2) eat sugary snacks between meals, 3) consume sugary drinks between meals, 4) receive topical fluoride from a health professional, 5) visit the dentist, and 6) not have an employed adult in the household. PCGs of children enrolled in Medicaid were significantly more likely to be the mother, have bleeding gums, eat sugary snacks between meals, consume sugary drinks between meals, eat or drink something other than water before going to bed, and not get regular dental checkups. In conclusion, there are significant differences in caries risk questionnaire responses based on Medicaid status and race/ethnicity that provide construct and criterion validity to the developed caries risk tool (ClinicalTrials.gov NCT01707797).